Zdravljenje z matičnimi celicami - Šimc, Mojca (Zdravniški vestnik, 2012)
Despite the progress in medicine, we are nowadays still faced with diseases and injuries, where with the knowledge, drugs and support technology availableto us, we cannot achieve the desired quality of patientćs life. Progress in stem cell biology may be the hope for certain diseases in the future. The purpose of this article is to present a rapidly advancing field ofstem cells. We summarize the properties of stem cells, various types of stemcells according to their origin from the embryonic or adult tissues, and according to their differentiation potential. Although numerous factors that determine the properties of stem cells are currently already known, we still need to know more about their mutual impact. We present the fields of clinicalmedicine where stem cells are already used for treatment, as well as those, for which there is, a justified hope that stem cell therapy will becomepart of routine treatment in the near future. The greatest potential of stem cells is probably their use in the treatment of degenerative diseases andtraumatic injuries, where we expect a major impact on the patientćs qualityof life. Similarly, the knowledge of stem cells has also contributed tounderstanding cancer diseases and thus open up opportunities for new approach to treating these diseases.
Keywords: Autoimmune Diseases; Avtoimunske bolezni; Biomedical Engineering; Biomedicinska tehnologija; celično zdravljenje; Hematologic Diseases; hematologija; Hematološke bolezni; Hematopoetska matična celica, presaditev; Hematopoietic Stem Cell Transplantation; Matične celice; Stem Cells; therapy; Transplantation; zdravljenje